Re-Exploring the Early Relationship between Teenage Cigarette and E-Cigarette Use Using Price and Tax Changes - Michael Pesko; Casey Warman (Institute of Labor Economics (IZA), 2021)
In 2016, the Surgeon General used longitudinal cohort studies to conclude that youth e-cigarette use is strongly associated with cigarette use. We re-evaluate data from the period of time before the writing of the Surgeon General report, using quasi-experimental methods, and reach the opposite conclusion. We study contemporaneous and intertemporal effects of e-cigarette and cigarette price and tax changes. Our price variation comes from 35,000 retailers participating in the Nielsen Retail Scanner data system. We match price and tax variation to survey data on current use of e-cigarettes and cigarettes for over 94,000 students between grades 6 to 12 in the National Youth Tobacco Survey (NYTS) for years 2011 to 2015. We find evidence that e-cigarettes and cigarettes are same-period economic substitutes. Coefficient estimates (while imprecisely estimated) also suggest potentially large positive effects of past e-cigarette prices on current cigarette use, indicating inter-temporal economic substitution. Our findings raise doubts about the conclusion of government-sponsored reports that e-cigarettes and cigarettes are strongly positively associated. We recommend revisiting and possibly amending this conclusion.
Keywords: I18; H71; 330; tobacco control; cigarette use; e-cigarette use; tax policy